2009
DOI: 10.1186/1472-6963-9-97
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of districts in implementing a national incentive programme to promote safe delivery in Nepal

Abstract: BackgroundNepal's Safe Delivery Incentive Programme (SDIP) was introduced nationwide in 2005 with the intention of increasing utilisation of professional care at childbirth. It provided cash to women giving birth in a health facility and an incentive to the health provider for each delivery attended, either at home or in the facility. We explored early implementation of the programme at the district-level to understand the factors that have contributed to its low uptake.MethodsWe conducted in ten study distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 20 publications
2
109
0
3
Order By: Relevance
“…There is concern as to whether the programs can be difficult to implement in countries with limited resources where the governments lack the staff, skills, and systems to manage and monitor services, payments, and performance. This was the case with a maternity incentive payment in Nepal, 19 where the "less poor" benefited more than the poor. 20 Further concerns are whether changes will be sustained over time and whether incentives are also useful for more complex services.…”
Section: Financial Incentives For Households and Providersmentioning
confidence: 99%
“…There is concern as to whether the programs can be difficult to implement in countries with limited resources where the governments lack the staff, skills, and systems to manage and monitor services, payments, and performance. This was the case with a maternity incentive payment in Nepal, 19 where the "less poor" benefited more than the poor. 20 Further concerns are whether changes will be sustained over time and whether incentives are also useful for more complex services.…”
Section: Financial Incentives For Households and Providersmentioning
confidence: 99%
“…Some of the more well-known programmes are Advance in Labour and Risk Management (ALARM) [18], Making It Happen [19], Practical Obstetric Multi-Professional Training (PROMPT) [20] and ALSO (Advanced Life Support in Obstetrics) [21]. There are also country-specific programmes such as Nepal's Safe Delivery Incentive Programme (SDIP) [22], Tanzania's comprehensive emergency obstetric and newborn care (CmONC) scale-up programme [23], and South Africa's Essential Steps in the Management of Obstetric Emergencies (ESMOE) [24].…”
Section: Programmesmentioning
confidence: 99%
“…Engagement with the community and "understanding … the needs of the target beneficiaries" (p 266) [5] is critical for understanding the potential barriers within the community that must be overcome to make the service accessible [6]. Women need to first deliver in facilities [40], and encouraging this practice may require consideration to lateral incentives [22] before facility-based scale up has a penetrating effect. Once willing to deliver in a facility, women and communities must be educated about where to deliver related to a risk assessment so that no undue burden is placed on a select group of care providers [16].…”
Section: Awareness Across the Boardmentioning
confidence: 99%
“…However, it also concluded that careful linking of benefits to needs of target populations is essential if improved financial protection and health status are to be achieved; and that highly focused interventions can be an important early step in this direction. Several countries in Latin America and Asia have indeed, in addition to providing a universal entitlement to health services, also introduced additional financial incentives to vulnerable groups -especially women and children (Bradshaw, 2008;Lomelí, 2008;Powell-Jackson, Morrison, Tiwari, Neupane, & Costello, 2009).…”
Section: Uhc -The Challenge Of Path Dependencementioning
confidence: 99%
“…An important concern is that services expansion in the name of UHC might actually worsen quality of services, or cut corners on medical ethics. For instance, there is a concern about some of the consequences of the growing popularity of demand-side financing, now spreading rapidly from Latin America (Bradshaw, 2008;Lomelí, 2008) to Asia (Ahmed & Khan, 2011;Powell-Jackson et al, 2009) and Africa Obare et al, 2013). Effective demand-side financing can significantly increase the demand for services as it did under various programmes in Latin America (Frenk, González-Pier, Gómez-Dantés, Lezana, & Knaul, 2006;Lomelí, 2008) and more recently in India under the Janani Suraksha Yojana programme (Lim et al, 2010).…”
Section: Uhc -The Challenge Of Path Dependencementioning
confidence: 99%